Nghiên cứu sự phân bố hàm lượng của các nguyên tố Ca, Cd, Cu, Fe, Mg, Mn, Mo, Pb và Zn trong các mẫu rau của Đà Lạt - Nguyễn, Giằng (Trường Đại học Đà Lạt, 2012)
Vegetable samples were collected form 11 locations of Dalat, including two kinds of vegetables (goods and safety) in both the summer and winter of 2003. The concentrations of elements were determined by Radiochemical Neutron Activation Analysis (RNAA) and Atomic Absorption Spectrometry (AAS). The elements analyzed were as follows: Ca , Cd, Cu, Fe , Mg. Mn, Pb and Zn by AAS and Mo by RNAA. Average concentration of Ca - 24 0 rug/kg wet, Cd -0.035 m g/kg wet, Cu - 0 .67 mg/kg wet, Fe - 8. 1 mg/kg wet , Mg - 131 rn g/kg wet, Mn - 3 . 1 mg/kg wet, M o -0.1 09mg/kg wet, Pb -0.345 mg/kg wet and Zn - 3 .0mg/kg wet.